The presbyteral ministry in the Church-Family of god in Côte d’Ivoire : a re-reading of the second Vatican council's Presbyterorum ordinis decree : theological challenges and ecclesiological perspectives - (:unkn) unknown (My University, 2022)
This work aims to be the first systematic and ecclesiological approach to the ministry of Ivorian priests with a view to necessary self-criticism. The credibility and relevance of their message depend on it. It is a question of detecting in the reality of the African family and in the concept of the Church- Family of God, key elements capable of enabling us to determine a face of the Ivorian priests for a Church closer to the men and women of the Côte d'Ivoire. We believe that the anchor on which we can rely is brotherhood. Thus, for us, the image of the “brother” priests would be more expressive from the perspective of a theology of the Church-Family of God in Côte d'Ivoire because the fraternal dimension of their ministry would encourage them to put themselves in the. Service of the people of God. Our reasoning could result in the introduction of a possible African ecclesiology from the ministry of priests. This ecclesiology could be perceived as an ecclesiology of the accompaniment of brothers and sisters on the way to the Father, embracing the notion of movement, of dynamism. The Church of Africa is called upon to become a Church of proximity, witness to the presence of God at the heart of humanity.
Keywords: African Research